Analysis of gut-associated fungi from Chinese mitten crab Eriocheir sinensis. Issue 1 (1st January 2021) - Xu, Shihan; Wang, Xiao; Nageen, Yumna; Pecoraro, Lorenzo
Abstract : Chinese mitten crab, Eriocheir sinensis ( Varunidae ), is one of the most popular and widely cultivated freshwater crab species in the Chinese food industry, with high commercial importance and nutritional value. We analyzed the diversity of culturable fungi in the gut of E. sinensis collected from a rice-crab co-culture system in Tianjin, China. We isolated 41 fungal strains from the gut of analyzed male and female crabs, using the dilution plate method. Morphological and molecular identification based on nuclear ribosomal internal transcribed spacer (ITS) sequencing suggested that these isolates belonged to 16 genera in Ascomycota, Basidiomycota, and Mucoromycota. Aspergillus was the dominant identified genus followed by Penicillium and Talaromyces. Yeasts, including Candida, Clavispora, Meyerozyma, and Trichosporon genera, accounted for a significant portion (12.2%) of the isolated strains . Statistical analysis showed significant differences in gut-associated fungal communities between female and male crabs, with female individuals showing a higher species diversity. Our study represents the first report on intestinal fungal communities of Chinese mitten crab, providing valuable microbiological information that could be essential for supporting the effective management and conservation of this crab species, and for the improvement of the economic performance of the crab industry.